Improvements of transmit efficiency and receive sensitivity with ultrahigh dielectric constant (uHDC) ceramics at 1.5 T and 3 T. Issue 5 (25th September 2017) - Rupprecht, Sebastian; Sica, Christopher T.; Chen, Wei; Lanagan, Michael T.; Yang, Qing X.
Abstract : Purpose: Incorporating high dielectric constant (HDC) materials into radiofrequency (RF) coils has been shown to effectively improve RF coil performance at 7 and 3 T because of the induced displacement current in the high dielectric constant materials. The displacement current is proportional to the RF field frequency and permittivity of the material. The aim of this paper is to investigate the effect of high dielectric constant materials with even greater permittivity on the RF field at 1.5 T and 3 T. Methods: Several monolithic ceramic materials with an ultrahigh dielectric constant ranging from 1200 to 3300 were investigated at 1.5 T and 3 T with phantom and human brain imaging along with computer modeling. Results: Experimental measurements in phantom studies showed a significant enhancement of signal‐to‐noise ratio (50–100%) and strong transmission power reduction (3–27‐fold). Under suboptimal experimental conditions in this study, the signal‐to‐noise ratio in the human brain cortex was nearly doubled, which produced high‐resolution image without the associated stronger magnetic susceptibility artifacts and elevated specific absorption rate concerns at higher field strengths. Conclusions: Use of ultrahigh dielectric constant ceramic materials is a simple and low‐cost approach that could further improve the RF technology to maximize image signal‐to‐noise ratio and reduce RF energy deposition for human studies. Magn Reson Med 79:2842–2851, 2018. © 2017 International Society for Magnetic Resonance in Medicine.